2009
DOI: 10.1542/peds.2008-1839
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts About End-of-Life Decisions in NICUs in the Netherlands

Abstract: The parents were involved in all EoL decision-making processes, and consensus was ultimately reached in all cases. Conflicts within the team occurred in 4% of the cases and between the team and the parents in 12% of the cases. The conflicts were resolved by postponing the EoL decision until consensus was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 38 publications
5
44
3
Order By: Relevance
“…Verhagen et al reported the outcome of the 150 deaths following an end-of-life decision by a retrospective notes review; 56% were infants who were unstable and were said to have no chance of survival and 44% were stable babies with poor prognosis 34. In a similar study, Weiner et al 35 noticed that 52% of infants that died following limitation of LST were unstable, which is comparable to the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Verhagen et al reported the outcome of the 150 deaths following an end-of-life decision by a retrospective notes review; 56% were infants who were unstable and were said to have no chance of survival and 44% were stable babies with poor prognosis 34. In a similar study, Weiner et al 35 noticed that 52% of infants that died following limitation of LST were unstable, which is comparable to the present study.…”
Section: Discussionsupporting
confidence: 83%
“…This outcome confirms the finding of earlier studies that physicians make considerable efforts to prevent potential conflicts from escalating. [46][47][48] Seen in this light, the choice of physicians to come forward to the wishes of the parents who Our study suggests that in most cases parents' intense emotions of anxiety, grief, and distress did not hinder them from asking relevant questions and from clearly explaining their considerations and preferences. It could even be argued that these emotions, especially the parents' fear of losing their child and their anxiety of seeing their child suffer, heightened their alertness and awareness.…”
Section: Discussionmentioning
confidence: 79%
“…Within the professional team, views may differ on the chances of survival and, more often, on the quality of life if the child survives. 7,8 The decision that further treatment is becoming futile is therefore not a 1-step decision: it takes time and repeated team discussions to realize that this is the case. In almost all situations, professional teams will be able to reach a consensus despite possible differences.…”
Section: Eol Decision-makingmentioning
confidence: 99%